Technology Based on Education Management and Islamic Boarding School Dalam Mencetak Peserta Didik Yang Unggul Melalui Program Unggulan (Prodistik) di Madrasah Aliyah Zainul Hasan 1 Genggong - Putri, Habibah; Izzah, Ismatul; Rachman, Poppy (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
This research aims to explore the effectiveness of distinctive flagship programs, focusing on how technology integration contributes to cultivating outstanding and pesantren-spirited students through the Prodistik program. The research method employed a qualitative approach, utilizing data collection techniques such as participatory observation and in-depth interviews with students, educators, and Prodistik heads to gain a comprehensive understanding and stakeholders' perceptions of technology-based and pesantren-integrated education management in shaping outstanding students at Madrasah Aliyah Zainul Hasan Genggong. The findings indicate that the implementation of technology-based and pesantren-integrated education management at the madrasah successfully merges traditional values with technology and serves as an inspiration for other educational institutions. This success is evidenced by graduates proficient in technology with a pesantren spirit, easily accepted in the workforce and universities.